Efficacy and safety of nesiritide in patients with decompensated heart failure: a meta-analysis of randomised trials - Gong, Bojun (BMJ Open, 2016)
OBJECTIVES: Current evidence suggests that nesiritide may have effects on renal function and decrease the incidence of mortality. However, a clear superiority using nesiritide in terms of renal toxicity and mortality in patients with heart failure was not consistently proven by previous studies. We performed a meta-analysis of all randomised trials to obtain the best estimates of efficacy and safety of nesiritide for the initial treatment of decompensated heart failure. METHOD: We performed a meta-analysis of randomised trials of nesiritide in patients with decompensated heart failure (n=38 064 patients, in 22 trials). Two reviewers independently extracted data. Data on efficacy and safety outcomes were collected. We calculated pooled relatives risk (RRs), weighted mean difference and associated 95% CIs. RESULTS: Compared with placebo, dobutamine and nitroglycerin, nesiritide indicated no increasing risk of total mortality. Compared with the combined control therapy, nesiritide was associated with non-significant differences in short-term mortality (RR 1.24; 95% CI 0.85 to 1.80; p=0.27), mid-term mortality (RR 0.86; 95% CI 0.60 to 1.24; p=0.42) and long-term mortality (RR 0.94; 95% CI 0.75 to 1.18; p=0.61). Nesiritide therapy increased the risk of hypotension (p<0.00 001) and bradycardia (p=0.02) when compared with control therapy. Compared with dobutamine or placebo therapy, no differences in serum creatinine, blood urea nitrogen and creatinine clearance, and no risk of the need for dialysis was observed in nesiritide therapy. CONCLUSIONS: Our findings indicated that, in patients with heart failure, nesiritide was not associated with the risk of mortality. However, it increased the risk of cardiovascular adverse events. The change of serum creatinine and creatinine clearance had no significant difference, and no risk of the need for dialysis was observed after low-dose nesiritide treatment.